Prevalencia de caries dental en niños de la clínica de la Universidad Antonio Nariño, en la ciudad de Bucaramanga 2023-1 (2023)
Introduction: Dental caries affects a large part of the world population, mainly the child population. Objective: To determine the prevalence of dental caries in children at the Antonio Nariño University clinic, 2023. Materials and methods: Descriptive cross-sectional study with 60 children treated at the clinic in the company of parents and/or caregivers. Instrument with a section on sociodemographic aspects and factors associated with caries previously reported in the literature. Absolute frequencies and percentages were calculated. Study without risk (Resolution 8430/1993). Results: Participation of the male sex (51.7%), average age 8 years (SD 2.06) and parents with secondary education (60.8%). Prevalence of dental caries of 88.3% (COP index), frequency of consumption of sugary drinks (76.7%) and dental brushing twice a day (46.7%). Conclusions: There is a high prevalence of dental caries that could be associated with lifestyles such as poor hygiene and consumption of sweets.